Función y papel del contrato en el Fundamento del Derecho natural de Fichte (1796): las aporías del contractualismo fichteano - Felipe Schwember Augier (Tópicos, 2014)
Fichte uses profusely different versions of the social contract when drafting his doctrine of right in the Foundations of the Natural Right (1796). This usage, which seems to follow a typical strategic reasoning of the hobbesian contractarianism, seems to be at odds with the altruistic reasoning employed in the first part of the work, in which it deduces the concept of right from mutual recognition. Here we attempt to demonstrate that there is no break between the deduction of right and its systematic application, and that the motive of self-preservation and the use of contract are in principle compatible with the deduction of right as technical practical science by Fichte. It will be argued, however, that the use of the social contract as a tool to develop a material doctrine of right is problematic, not for the motivations that are supposed to be attributed to the agents, but for the gap that this use opens in the methodological presuppositions of the work and its normative claims.